Friction of Ionic Liquid–Glycol Ether Mixtures at Titanium Interfaces: Negative Load Dependence. Issue 14 (4th May 2018) - An, Rong; Zhou, Guobing; Zhu, Yudan; Zhu, Wei; Huang, Liangliang; Shah, Faiz Ullah
Abstract: The atomic force microscopy experiments and nonequilibrium molecular dynamics (NEMD) simulations demonstrate a negative friction–load dependence to ionic liquid–glycol ether mixtures, that is, the friction decreases as the normal load increases. NEMD simulations reveal a structural reorientation of the studied ionic liquid (IL): as the normal load increases, the cation alkyl chains of ILs change the orientation to preferentially parallel to the tip scanning path. The flat‐oriented IL structures, similar to the "blooming lotus leaf, " produce a new sliding interface and reduce the friction. A further molecular dynamics simulation is carried out by adopting slit‐pore models to mimic the tip approaching process to confirm the dynamics of ILs. A faster diffusion of ILs in the smaller slit pore is observed. The faster diffusion of ILs in the more confined slit pore facilitates the structural reorientation of ILs. The resulted new sliding surface is responsible for the observed smaller friction at higher loads, also known as the negative friction–load dependence. These findings provide a fundamental explanation to the role of ILs in interfacial lubrications. They help to understand liquid flow properties under confinement, with implications for the development of better nanofluidic devices. Abstract : A negative "friction–load dependence" phenomenon is observed on titanium interfaces lubricated with ionic liquid–glycol ether mixtures. The faster diffusion of ionic liquids (ILs) at higher normal loads facilitates the structural reorientation of the IL cations, and the resulted new sliding surface to the tip is responsible for the observed negative situation.